Stepfather Involvement and Stepfather-Child Relationship Quality: Race and Parental Marital Status as Moderators - Jensen, Todd M. (J Marital Fam Ther, 2016)
Stepparent-child relationship quality is linked to stepfamily stability and children’s well-being. Yet, the literature offers an incomplete understanding of factors that promote high quality stepparent-child relationships, especially among socio-demographically diverse stepfamilies. In this study we explore the association between stepfather involvement and stepfather-child relationship quality among a racially diverse and predominately low-income sample of stepfamilies with pre-adolescent children. Using a subsample of 467 mother-stepfather families from year 9 of the Fragile Families and Child Wellbeing Study, results indicate that stepfather involvement is positively associated with stepfather-child relationship quality. This association is statistically indistinguishable across racial groups, although the association is stronger among children in cohabiting stepfamilies compared to children in married stepfamilies.